2022
DOI: 10.1038/s41598-022-22935-1
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic individual variation in daily activity onset and plastic responses on temporal but not spatial scales in female great tits

Abstract: In a variety of species, individuals appear to be consistent in the daily timing of their activity onset. Such consistent among-individual differences can result from both intrinsic factors, as individuals may e.g. differ genetically, and extrinsic factors, as the environment may vary on spatial and temporal scales. However, previous studies typically did not differentiate between their respective contributions on individual variation in the timing of activities. Here, we repeatedly measured the onset of activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…As timing of activity is thought to be consistent we expected that individuals with relatively early timing during the egg laying phase would also be early during the pre-egg laying phase. We showed that emergence time is repeatable on the long term (i.e., across years) in female great tits in our population (Meijdam et al, 2022). Therefore, we decided to measure emergence and entry times mainly during the egg laying phase.…”
Section: Emergence and Entry Timesmentioning
confidence: 95%
“…As timing of activity is thought to be consistent we expected that individuals with relatively early timing during the egg laying phase would also be early during the pre-egg laying phase. We showed that emergence time is repeatable on the long term (i.e., across years) in female great tits in our population (Meijdam et al, 2022). Therefore, we decided to measure emergence and entry times mainly during the egg laying phase.…”
Section: Emergence and Entry Timesmentioning
confidence: 95%
“…In particular, they delay their activity onset and advance their offset throughout incubation, while responses to environmental factors, such as temperature and rain fall, additionally increase variation between days. This large plasticity in females is also reflected in their repeatability of onsets ranging from 0.13 to 0.46 and offsets from 0.00 to 0.37 (Meijdam et al, 2022; Schlicht & Kempenaers, 2020; Stuber et al, 2015). It is important to experimentally disentangle daily effects from those of ALAN by looking at between‐ as well as within‐individual responses.…”
Section: Introductionmentioning
confidence: 99%